Warisan Paradigmatik Kebijakan Politik Kerukunan Antara Agama Kolonial Pada Masa Reformasi - Munawir Haris (TASAMUH: Jurnal Studi Islam, 2017)
In the matter of political harmony, the emergence of policies variety that smelled past at least it is sufficient evidence that the policy line of the sustainability paradigm. KUB bill that many feared would make a significant setback, indeed fail enacted. However, the advent of the Joint Regulation of the Minister of Religious numbers 9 and Minister of the Interior No. 8 of 2006, which revised the decree number 1 in 1979, seems to have been present the past in the midst of this reform. At the beginning of the reforms, the changes were encouraging, especially during the reign of Abdurrahman Wahid (1999-2001). Gus Dur did significant movement to repeal Presidential Decree No. 14 of 1967 On Religion, Beliefs and Customs of China through Presidential Decree No. 6 of 2000 dated 17 January 2000. Since that time, the rapidly growing Chinese culture, including religious activities. In the reign of Gus Dur, as K.H. Tolhah Hasan served as Minister of Religion, once there is a suggestion that the government (in this case the Ministry of Religion) ratified the United Nations Declaration on the elimination of various forms of intolerance or disharmony and discrimination based on religion or belief (endorsed 25 November 1981). It is an initiative developed from the Ministry of Religious Affairs (MORA Now) to guarantee the principle that no one should be subjected to discrimination by the state, institution, group of persons, or person on grounds of religion or other beliefs.